Adrenal cysts-a report of four cases including one with bilateral involvement - Fernandes, Gwendolyn; Chaudhari, Jayashri; Shah, Nalini; Gupta, Akriti (International Journal of Medical Research and Review, 2016)
Adrenal cystic lesions are rare entities. Four types of cystic lesions of the adrenal gland have been described in literature namely, epithelial cysts, endothelial cysts, pseudocysts and parasitic cysts. Tumors of the adrenal gland, both benign and malignant may also show cystic change and have to be considered in the differential diagnosis of cystic lesions of the adrenal gland. Lymphangioendotheliomas, though common at other sites, are unusual in the adrenal glands and bilateral involvement is extremely rare. We present four cases of adrenal cysts, two cases of lymphangioendothelial cysts and two cases of pseudocysts from 108 adrenalectomy specimens received over 5 years. Two of these had hypertension which resolved after surgery. All of our cases did well postoperatively. Prognosis of these benign cysts is excellent and the patients are disease-free after surgery.